SISTEM INFORMASI AKADEMIK SISWA BERBASIS SMS GATEWAY PADA MADRASAH ALIYAH BATANG KABUNG - Elmawati Elmawati; Eko Amri Jaya (Jurnal Sains dan Teknologi: Jurnal Keilmuan dan Aplikasi Teknologi Industri, 2020)
In improving the quality of education to be better, one of them is by overcoming the problem of students who are not disciplined like truant students and if given a summons letter parents are often students who give the letter to the party representing their parents. Making this application is done on the basis of analysis and observations made at the Madrasah Aliyah Batang Kabung with a focus on the problem of attendance or student attendance. The purpose of making this application is to be able to connect or facilitate between the school and the parents in sharing information, so parents can find out the development of their children's studies at school. The steps taken in this study are system analysis and planning, needs analysis, system design, implementation, integration and testing. With the construction of student academic information systems based on sms gateway can facilitate student guardians in terms of accessing academic information so that it can be done anytime and anywhere directly and up to date.